The Expression Change of Mmp-8 and Collagen Type-2 Intracell in Lung Tissue Due to Electronic Smoke Exposure - Suryadinata, Rivan Virlando; Wirjatmadi, Bambang; Andriani, Merryana; Sumarmi, Sri (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The number of electronic smokers has increased annually. Exposure to an electronic cigarette will increase free radicals in the body and result in oxidative stress causing lung tissue damage. The severity degree of lung tissue damage caused by electronic smoke exposure depends on the duration of electronic cigarette smoke exposure, and will affect Matrix Metalloproteinase-8 and collagen type-2 in the cells. The study aims to understand the change degree of Matrix Metalloproteinase-8 and collagen type-2in lung tissue due to electronic cigarette smoke exposure. This study applied the experimental method with a post control group design. The male Wistar rats were used as the animal models in this research to assess cell damage through the Matrix Metalloproteinase-8 expression and collagen type-2 in the lung tissue using immunohistochemical staining. Exposure to electronic smoke cigarettes was given to each group of animal models with the difference in amount and time duration. The expression of Matrix Metalloproteinase-8 indicated a significant increase due to electronic smoke exposure (ANOVA, p=0.000). Meanwhile the expression of collagen type-2 showed a significant decrease because of electronic smoke exposure (ANOVA, p=0.000). Besides, MMP-8 and collagen type-2 manifested relationship existence and strong impact (r=0.948, p=0.000).  The negative impact of exposure to electric cigarette smoke causes increased expression of Matrix Metalloproteinase-8 and decreased expression of type-2 collagen in lung tissue.